Microvascular response to exercise varies along the length of the tibialis anterior muscle. (25th July 2022) - Veeger, Thom T. J.; Hirschler, Lydiane; Baligand, Celine; Franklin, Suzanne L.; Webb, Andrew G.; de Groot, Jurriaan H.; van Osch, Matthias J. P.; Kan, Hermien E.
Abstract : Microvascular function is an important component in the physiology of muscle. One of the major parameters, blood perfusion, can be measured noninvasively and quantitatively by arterial spin labeling (ASL) MRI. Most studies using ASL in muscle have only reported data from a single slice, thereby assuming that muscle perfusion is homogeneous within muscle, whereas recent literature has reported proximodistal differences in oxidative capacity and perfusion. Here, we acquired pulsed ASL data in 12 healthy volunteers after dorsiflexion exercise in two slices separated distally by 7 cm. We combined this with a Look‐Locker scheme to acquire images at multiple postlabeling delays (PLDs) and with a multiecho readout to measure T2 *. This enabled the simultaneous evaluation of quantitative muscle blood flow (MBF), arterial transit time (ATT), and T2 * relaxation time in the tibialis anterior muscle during recovery. Using repeated measures analyses of variance we tested the effect of time, slice location, and their interaction on MBF, ATT, and T2 *. Our results showed a significant difference as a function of time postexercise for all three parameters (MBF: F = 34.0, p  < .0001; T2 *: F = 73.7, p  < .0001; ATT: F = 13.6, p  < .001) and no average differences between slices over the total time postexercise were observed. The interaction effect between time postexercise and slice location was significant for MBF and T2 * (F = 5.5, p  = 0.02, F = 6.1, p  = 0.02, respectively), but not for ATT (F = 2.2, p  = .16). The proximal slice showed a higher MBF and a lower ATT than the distal slice during the first 2 min of recovery, and T2 * showed a delayed response in the distal slice. These results imply a higher perfusion and faster microvascular response to exercise in the proximal slice, in line with previous literature. Moreover, the differences in ATT indicate that it is difficult to correctly determine perfusion based on a single PLD as is commonly performed in the muscle literature. Abstract : We used quantitative arterial spin labeling to assess microvascular response to exercise at two locations of the tibialis anterior (TA) muscle. We found initial increased muscle blood flow (MBF) and slower microvascular response to exercise proximally in the TA, indicating regional differences. Arterial transit time (ATT) was decreased after exercise and different between slices. This indicates that commonly used single postlabeling delay measurements have a risk of underestimating perfusion or finding perfusion differences influenced by changes in ATT.